Use of Gamification Model for Homeroom Teacher in Conducting Learning Assessment (Qualitative Study) - Retno Ariyanti Nurningtias; Hudzaifi Syah Tsalits Taufiqi; Muhammad Raihan Zaki; Rizki Hikmawan (Universitas Sebelas Maret, 2022)
Gamification is a game element but is included in non-game contexts because it is an effective motivational tool. The performance performed by using gamification becomes more attractive to users. The focus of the problem is determined by the researcher based on the field of education, with the object of research being a homeroom teacher. Education standards are at the level all stakeholders require, especially learning assessment. Education standards are at the level all stakeholders require, especially learning assessment. The urgency of students who are entitled to an evaluation from the teacher and easily known by the school and forwarded to parents. The approach taken with a qualitative study provides a more detailed explanation to homeroom teachers about problem solutions to place gamification in student learning assessments. Data were collected based on experiments with several homeroom teachers feeling and exploring media. The finding of homeroom responses which are very satisfied with gamification encourages entering students' grades in a fun way. From the study results, the application of gamification strategies in which homeroom teachers conduct learning assessments triggers interest in fun characters, overcomes boredom with challenges and competition, gains new knowledge, and improves thinking skills to strengthen social interaction.